Hypertension in chronic kidney disease - Schaefer, Franz; Mehls, Otto (Pediatric Hypertension, 2004)
Persistent arterial hypertension (HTN) is observed in approx 0.1% of children. In contrast to adults, secondary forms of HTN are more frequent than essential HTN, which accounted for only 20% of cases in a meta-analysis of 1575 children and adolescents compiled from nine published studies (1). Essential HTN is diagnosed almost exclusively in adolescent patients, whereas secondary causes prevail in prepubertal children.